2021
DOI: 10.1111/cen.14491
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymph node ratio in children and adolescents with papillary thyroid cancer

Abstract: Objective Neck lymph node (LN) metastasis is a common feature of paediatric papillary thyroid cancer, and LN ratio (LNR) is defined as the ratio of the number of positive LNs excised to the total number of removed. Unlike in adults, few data are available regarding the clinical implication of LNR in the paediatric population. Our purpose was to investigate the association of LNR with clinical outcomes in paediatric papillary thyroid cancer. Design & Methods The study retrospectively reviewed 136 consecutive ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
2
5
1
Order By: Relevance
“…Because of an increasing incidence of PTC in this age group, documentation of the prognosis and identification of predictors of DFS are of great clinical value. Our results showed that age at diagnosis, positive preoperative TSH level, maximal tumor size >2 cm, number of central and lateral LNM, lateral LNM, and N staging were risk factors for recurrence, similar to other research findings ( 20 22 ). In addition, we also found that the ATA pediatric risk stratification had predictive value for recurrent PTC patients in children and adolescents, the same results as other scholars’ research ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Because of an increasing incidence of PTC in this age group, documentation of the prognosis and identification of predictors of DFS are of great clinical value. Our results showed that age at diagnosis, positive preoperative TSH level, maximal tumor size >2 cm, number of central and lateral LNM, lateral LNM, and N staging were risk factors for recurrence, similar to other research findings ( 20 22 ). In addition, we also found that the ATA pediatric risk stratification had predictive value for recurrent PTC patients in children and adolescents, the same results as other scholars’ research ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we also found that the ATA pediatric risk stratification had predictive value for recurrent PTC patients in children and adolescents, the same results as other scholars’ research ( 22 , 23 ). Multivariate analysis demonstrated that younger age (<14 years) at diagnosis and positive preoperative TSH were independent risk factors for recurrence, which were consistent with the results of other studies ( 20 25 ). The prognosis of pediatric PTC is generally excellent.…”
Section: Discussionsupporting
confidence: 90%
“…However, unlike previous studies 25 , the lymph node metastasis rate of our study cohort did not suggest recurrence, which may be due to the different number of lymph node dissections.…”
Section: Discussioncontrasting
confidence: 99%
“…Prognostic factors, including RMLN, tumor extent, lateral lymph node involvement, and multifocal disease, have been reported to be associated with outcomes in the literature. 12,16,17 Shukla et al reported that decreasing age was related to the burden of nodal disease and the risk of extensive neck metastasis. 18 Redlich et al showed that younger age had an independent association with greater risk of recurrence and progression.…”
Section: Discussionmentioning
confidence: 99%